Transformasi Paradigma Pembangunan Ekonomi: Membangun Masa Depan Berkelanjutan melalui Perspektif Ekonomi Syariah - Amsari, Syahrul; Harahap, Isnaini; Nawawi, Zuhrinal M (Ekonomis: Journal of Economics and Business, 2024)
This article illustrates a paradigm shift in economic development through the lens of Islamic Economics, with a specific focus on sustainable development. The background involves a profound understanding of global economic challenges and the necessity to construct a sustainable development foundation from the perspective of Islamic economic values. The research aims to analyze the contribution of Islamic Economics in addressing economic imbalances, poverty alleviation, and community empowerment. The research methodology entails an in-depth literature review and a critical analysis of existing development models. The findings of this study indicate that the implementation of Islamic Economic concepts has the potential to foster more inclusive and sustainable economic growth. Factors such as distributive justice, community participation, and environmental sustainability take center stage in shaping Shariah-based economic policies. In this context, the article also identifies innovations and best practices in applying Islamic Economic principles to economic development. The conclusion of this article summarizes that the transformation of the economic development paradigm through the Islamic Economics approach can create a robust foundation for sustainable development. The primary contributions lie in achieving economic justice, community empowerment, and environmental sustainability. Thus, this article makes a significant contribution by providing insights and a new direction for a more holistic and resilient approach to economic development.